Cellulose Elementary Fibrils as Deagglomerated Binder for High-Mass-Loading Lithium Battery Electrodes - Young-Kuk Hong; Jung-Hui Kim; Nag-Young Kim; Kyeong-Seok Oh; Hong-I Kim; Seokhyeon Ryu; Yumi Ko; Ji-Young Kim; Kwon-Hyung Lee; Sang-Young Lee (Nano-Micro Letters)
Highlights Cellulose elementary fibrils (CEFs), the most fundamental unit of cellulose, are proposed as a deagglomerated binder for high-mass-loading Li battery electrodes. The CEFs, due to their increased surface area and anionic charge density, promote uniform dispersion with carbon additives and mitigate interfacial side reactions in electrodes. The CEF-based overlithiated layered oxide cathode exhibits a high areal-mass-loading (50 mg cm–2) and a high specific energy density (445.4 Wh kg–1) of a cell.